O nomadismo de Carlos Magno nas vozes do cordel - Sousa, Willian Lima de (2013)
The present research aims at examining the popularity of Charlemagne‟s narrative in the Northeastern Brazilian scenario, as well as the process of nomadisms related to the narratives involving carolingian characters in the course between Europe - northeastern Brazil and its linguistic and cultural mouvence to the voice and letter that inhabits the popular imaginary of northeastern people. After the death of Charlemagne, and mainly, in the ninth century, a series of narratives involving this character and his companions began to circulate in some countries in Europe, starting in France. In this country, the narrative is relevant in importance for the development of popular literature. Fixed in the popular stratum in Portugal, the narratives involving Charlemagne begin their process of nomadism towards Brazil around 1769 and 1826. In Brazil, principally in the Northeast, the narrative is structured primarily on an oral support. According to Cascudo, the cantador‟s voice is the first support of this narrative. Returning to the pages of folhetos in 1909, the voice was fixed on the pages written by Leandro Gomes de Barros and it achieved a high rate of consumption amid the Northeastern community. These folhetos are sold today and are famous in Northeast lands, because these carolingian knights with their honor system, their costumes are updated on a mythically figure present in the Northeast popular imaginary, the cangaceiro. Based on these discussions, this research sought to understand two significant processes that involve these narratives, however anchored on Paul Zumhtor‟s concept of nomadism. First, the nomadism of carolingian narrative favors the actualization of the Charlemagne sign in the figure of northeastern cangaceiro. Second, if in this process nomadism of Charlemagne's narrative from the prose structure to verse structure, the catholic discourse current in the prose text is reissued in the Northeast folhetos. Through these two questions, the results reached in this dissertation demonstrate that the process of updating the myth of Charlemagne in the Cangaceiro figure, as well as the strength of the Catholic discourse favored the popularity of the Charlemagne folhetos in northeastern Brazil.